Fabrication of Aluminium LM6 Hollow Cylinder using Vertical Centrifugal Casting - Wan Mohamad Hanapi, Wan Muhamad Syakir; Jamian, Saifulnizan (Research Progress in Mechanical and Manufacturing Engineering, 2024)
The centrifugal casting method is one of the good fabrication methods for the production of cylindrical products. In this study, two Aluminum LM6 hollow cylinders were produced using the vertical centrifugal casting method with different processing parameters. Specimen 1 was produced by setting the motor speed to 1700 rpm and without mold pre-heating. While for Specimen 2, the motor speed was set at 1800 rpm with pre-heating of the mold at a temperature of 200°C. The Aluminum LM6 molten metal casting temperature for both specimens was set at 700°C. The mold was allowed to rotate for 30 minutes after casting and allowed to cool at room temperature before the specimen was removed. From the physical observation of both specimens show good quality surface finish but have small defects which are veining and joint flash possible causes of improperly heating mould. Overall, the quality surface area for both specimens have smooth surface area and good dimensional accuracy. Moreover, the cross-sectional microstructure parallel to the radial direction of the two Al LM6 cylinders were observed using a Scanning Electron Microscope (SEM). Both specimens have a non-uniform Si distribution in the longitudinal radial but the Si sizes in the outside, middle, and interior areas are different, which is Si is distributed in specimen 2 with an atomic weight of 20.67%, while Si is distributed in specimen 1 with an atomic weight of 14.78%. Due to the limited quantities of carbon and oxide present, the dispersion is also homogenous. Vickers micro hardness test was also conducted on the cross section parallel to the radial direction of the two Al LM6 cylinders. Specimen 1 has a hardness value of 5.732 HV, whereas specimen 2 has a lower hardness value of 6.437 HV. Both specimens have uniformity along the radial axis, although specimen 2 has greater uniformity in rising than specimen 1. The findings of this study show the importance of motor speed setting and pre-heating in producing good Aluminum LM6 cylinders.